Innovative Teaching Materials for Balaghah: Enhancing Literary Appreciation through Syawahid Adabiyah in Ilmu Badi' - Ulin Nuha, Muhammad Afthon; Ahmad Fikri Amrullah; Rizka Widayanti; Ida Fauziatun Nisa’; Murdiono Murdiono (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2024)
This study aims to develop innovative teaching materials for Balaghah and Ilmu Badi' using Syawahid Adabiyah to enhance literary appreciation among students in the Arabic Language Education Program at UIN Sayyid Ali Rahmatullah Tulungagung. The term "Syawahid Adabiyah" refers to examples from literary texts that serve as a foundation for understanding the beauty and intricacies of language, making it a valuable resource for students. This study formulates two main research questions: 1) What are the steps for developing and assessing the feasibility of Ilmu Badi's teaching materials? 2) What is the effectiveness of these developed materials in improving students' literary appreciation? To address these questions, the research employs the Research and Development (R&D) model by Borg and Gall, focusing on contextual and varied teaching materials that integrate literary examples as learning media. The results are expected to demonstrate that the developed materials are viable and significantly enhance students' interest and skills in analyzing and creating beautiful literary works. This study contributes positively to the broader field of Arabic language education in Indonesia by providing a comprehensive approach that combines theory and practice.